Discipleship as theological prolegomenon implications for the relation of theory and praxis in the work of Pascal, Kierkegaard, and Bonhoeffer - Dunn, Patrick (Stellenbosch : Stellenbosch University, 2018)
Thesis (PhD)--Stellenbosch University, 2018.